Mechanism and treatment of hypertriglyceridaemia in gout. Issue 1 (February 1979) - Gibson, T; Kilbourn, K; Horner, I; Simmonds, H A
Abstract : Using the Intralipid lipid tolerance test we could not demonstrate any direct effect of serum triglyceride on uric acid or any influence of hyperuricaemia on triglyceride removal. This result supports previous studies suggesting that hyperuricaemia and hypertriglyceridaemia are linked through the association of obesity and alcohol excess rather than a direct cause and effect mechanism. It was possible to demonstrate significant reductions of serum triglyceride in patients with gout by reducing either their alcohol intake or body weight. Reduction of serum uric acid by probenecid had no effect on serum triglyceride or cholesterol. Similarly, allopurinol had no significant effect on serum triglyceride, but a significant fall of serum cholesterol was observed.